Quantifying biomarkers in wildlife exposed to low doses of environmental radiation pilot study - Halim, Nadia, author; Johnson, Thomas, advisor; Brandl, Alexander, committee member; Lindsay, James, committee member (Colorado State University. Libraries, 2017)
Exposure of free-ranging wildlife to environmental radiation is of concern following the nuclear accident at the Fukushima-Daiichi facilities in 2011. The uncertainty associated with exposure to chronic ionizing radiation in the vicinity of the accident continues to concern the general population, as well as produce seemingly conflicting scientific results. The risk from prolonged, low dose/low dose rate radiation exposures, specifically to wildlife, remains relatively uncertain. The quantification of chromosomal aberrations such as dicentrics and micronuclei was evaluated as a method of estimating radiation dose to wild boar. Dicentrics and micronuclei found in blood samples of humans are known as a biomarkers of radiation exposure. Blood samples were collected from wild boar in two towns in Fukushima prefecture in Japan and from Kentucky in the USA. External dose was also estimated using soil sample analysis. As a pilot study, only the feasibility of using dicentrics and micronuclei to estimate radiation dose in wild boar was investigated. Additional studies will be required to ascertain the suitability of measuring other chromosomal aberrations and/or decreased telomere length as a method of ascertaining wild boar radiation dose. The hypothesis of the pilot study was that it is possible to estimate chronic radiation dose to wild boar exposed to low levels of lingering environmental ionizing radiation in Fukushima prefecture as well as in irradiated blood from wild boar residing in areas experiencing only natural background radiation with biodosimetry techniques. The data obtained from this investigation do not prove the feasibility of using dicentrics and micronuclei formation to estimate wild boar radiation dose. While the technique for processing wild boar blood in order to observe chromosomal aberrations was successful, the levels of radiation exposure to the wild boar were too low and did not produce biomarkers for use as an indicator of internal radiation dose indicating the hypothesis to be incorrect. Other methods of estimating low radiation dose to wild boar will need to be investigated in future studies.